Early clinical outcomes of Portico and Edwards Sapien 3 valve prosthesis in transcatheter aortic valve replacement: propensity-matched analysis - Primessnig, Uwe; Wiedenhofer, Julia M.; Trippel, Tobias D.; Loddenkemper, Carina M.; Schrader, Helene; Brand, Anna; Spethmann, Sebastian; Stangl, Karl; Haghikia, Arash; Landmesser, Ulf; Boldt, Leif-Hendrik; Blaschke, Florian; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction There is a lack of real-world data directly comparing different valve prostheses for transaortic valve replacement (TAVR). We aimed to compare early clinical outcomes at 30-days between the self-expandable Portico valve (Abbott) with the balloon-expandable Edwards Sapien 3 valve (Edwards Lifesciences) (ES3). Methods Out of 1,901 patients undergoing TAVR between January 2018 and December 2021, all patients who received either Portico valve or ES3 valve via transfemoral TAVR were matched using nearest-neighbor (1:1) propensity scoring. Primary endpoints were single safety endpoints and early safety composite endpoints defined by Valve Academic Research Consortium-2 (VARC-2) criteria. The secondary endpoint was to analyze risk predictors for new permanent pacemaker (PPM) implantation in TAVR. Results Out of 661 complete cases, a total of 434 patients were successfully matched based on age, sex, Euro Score II and STS-score. In the matched cohort, 217 received either a Portico or valve and 217 received an ES3 valve. The VARC-2 early safety composite scores indicated a significantly greater overall 30-day safety risk in the Portico group at 9.2% (n = 20) compared to 3.7% (n = 8) in the ES3 group (p = 0.032). The requirement for new permanent pacemaker (PPM) implantation was also higher in the Portico group, at 21.2% (n = 46) vs. 13.4% (n = 29) in the ES3 group (p = 0.042). 30-day mortality was higher was 3.7% (n = 8) in Portico group compared to 0.9% in ES3 group (p = 0.11). Furthermore, implantation of the Portico valve was identified as a significant risk predictor for new PPM implantation, alongside higher age, preprocedural atrioventricular block (AVB) and longer total procedure duration. Conclusion This study shows significantly higher rates of early clinical complications for Portico valve prostheses compared to ES3. These findings should be especially taken into consideration when selecting valve prosthesis for high-risk patients.